2013
DOI: 10.1186/1471-2458-13-29
|View full text |Cite
|
Sign up to set email alerts
|

Age at menarche and its relationship to body mass index among adolescent girls in Kuwait

Abstract: BackgroundDespite the increasing rates of childhood obesity and rapid change in socio-economic status, the mean age at menarche remains mostly unknown among contemporary girls in Kuwait and other countries in the Gulf region. This study aimed to estimate the mean age at menarche among schoolgirls in Kuwait and investigate the association between age at menarche and obesity.MethodsA cross-sectional study was conducted on 1,273 randomly selected female high school students from all governorates in Kuwait. Overwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
62
5
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 59 publications
17
62
5
7
Order By: Relevance
“…Our finding may be attributed to the fact that obesity among young women in Curacao is quite common. As many studies have shown that overweight may accelerate the maturation process, the effect of obesity may have overridden any effect of father absence (e.g., Al-Awadhi et al, 2013). However, we did not find that BMI was related to the age of menarche.…”
Section: Discussioncontrasting
confidence: 83%
“…Our finding may be attributed to the fact that obesity among young women in Curacao is quite common. As many studies have shown that overweight may accelerate the maturation process, the effect of obesity may have overridden any effect of father absence (e.g., Al-Awadhi et al, 2013). However, we did not find that BMI was related to the age of menarche.…”
Section: Discussioncontrasting
confidence: 83%
“…The result of this study is in accordance to the study done by Al-Awadhi et al, (2013) that stated that there is a relation between nutritional status and menarche age. The high BMI of a female adolescent in pre puberty could increase the supply production of estrogen inside their body.…”
Section: The Influence Of Family Incomesupporting
confidence: 92%
“…A study conducted in Kuwait among 1200 girls found that there was a delay in onset of menarche in obese and overweight girls. 21 This result was in contrast to the study conducted in US. 20 In our study, most of the girls did not know their weight or height at the time of menarche and therefore the BMI at the time of menarche could not be calculated.…”
Section: Discussionmentioning
confidence: 62%